Is M&A different during a crisis? Evidence from the European banking sector - Beltratti, Andrea; Paladino, Giovanna (Journal of Banking & Finance, 2013)
The financial crisis has affected the landscape of the banking sector around the world. We use a sample of transactions carried out by European acquirers in 2007–2010 to study the acquirer’s stock price market reaction to both announcements and completions of acquisitions. At the aggregate level, we find that there are no significant abnormal returns around the announcement of an acquisition while there are positive abnormal returns at completions. We study the cross-sectional determinants of abnormal returns and find that announcement returns are mainly explained by the acquirer bank characteristics, while completion returns mainly depend on opacity of the target and on the drop in idiosyncratic volatility associated with a reduction of uncertainty.